2000
DOI: 10.1212/wnl.54.2.438
|View full text |Cite
|
Sign up to set email alerts
|

α2 Macroglobulin and the risk of Alzheimer’s disease

Abstract: Our data support an association between the A2M gene and AD. This association is less pronounced, however, in our cohort than in the previously reported sample of sibpairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 30 publications
2
28
0
1
Order By: Relevance
“…These possibilities are not mutually exclusive and could help to explain the nearly compete suppression of the ApoE4 effect, if they occur in combination. Whereas this is the first report that ␣2M negatively interferes with neuronal cell death caused by AD gene products, this ␣2M antagonism against ApoE4 concurs with recent reports Liao et al, 1998;Alvarez et al, 1999;Dodel et al, 2000;Romas et al, 2000) that polymorphisms of ␣2M are genetically associated with AD, although this association is controversial (Kovacs et al, 1999;Gibson et al, 2000;Higuchi et al, 2000;Sodeyama et al, 2000).…”
Section: Discussionsupporting
confidence: 87%
“…These possibilities are not mutually exclusive and could help to explain the nearly compete suppression of the ApoE4 effect, if they occur in combination. Whereas this is the first report that ␣2M negatively interferes with neuronal cell death caused by AD gene products, this ␣2M antagonism against ApoE4 concurs with recent reports Liao et al, 1998;Alvarez et al, 1999;Dodel et al, 2000;Romas et al, 2000) that polymorphisms of ␣2M are genetically associated with AD, although this association is controversial (Kovacs et al, 1999;Gibson et al, 2000;Higuchi et al, 2000;Sodeyama et al, 2000).…”
Section: Discussionsupporting
confidence: 87%
“…Genetic association of A2M with AD was also noted in the Finnish elderly population [16]. Similar results were reported in the USA [5,7,13]. These data seem to support the view about susceptibility for AD, linked to A2M polymorphism.…”
Section: Introductionsupporting
confidence: 83%
“…Previous studies have indicated that there may be alterations in the levels of proteins that attenuate Ab fibrillization, namely a2M 155 and SAP 156 in AD patients, although there are also conflicting data on this issue. It should be noted that polymorphism in the a2M gene may be associated with AD risk in some populations and may be influenced by family history (for example references [157][158][159][160][161][162] ), although these findings are controversial. Decreased SAP levels have also been correlated with impaired cognitive performance in aged individuals 163 and in clinically diagnosed AD.…”
Section: Ab-binding Proteins In Blood Plasmamentioning
confidence: 99%